Diskriminasi Laki-Laki terhdap Perempuan: Perspektif Q.S. An-Nisa ayat 01 - Maryam, Ayu Siti (Maliki Interdisciplinary Journal, 2025)
Gender discrimination is a deep and complex social problem, affecting women’s lives in various aspects, both in public and domestic spaces. This article aims to analyze the Qur’an’s views on women’s rights and roles, and to identify forms of discrimination that still occur in society. Using a qualitative approach, this study collected data from Qur’anic interpretations, related literature, and relevant case studies. The results show that although the Qur’an affirms women’s equality and rights, discriminatory practices still occur, often triggered by deep-seated patriarchal social and cultural norms. This discrimination is not only carried out by men, but also by women themselves, who are influenced by stereotypes and societal expectations. This article suggests the need for gender equality education and advocacy to change people’s mindsets, as well as to enforce laws that protect women’s rights. Thus, it is hoped that a more just and equal environment for women can be created in all aspects of life.